Analisis Pemberian Insentif Tidak Kena Pajak Bea Balik Nama Kendaraan Bermotor Terhadap KBL Berbasis Baterai Di DKI Jakarta - Chairinaya Nizliandry (Widya Yuridika, 2020)
Taxes are the main source of state revenue in their function as budgetair and as a tool to regulate in the social and economic fields in their function as a regulator, which based on the collection agency is divided into central taxes and regional taxes. One form of regional tax at the provincial level is the title transfer tax for motorized vehicles, which on January 3, 2020, by the Governor of DKI Jakarta, is given a non-taxable incentive for the transfer of ownership of Battery-Based Electric Motor Vehicles for Road Transportation. By using a juridical-normative approach through the theory of legal validity, it can be seen that the issuance of Gubernatorial Regulation 3/2020 is contrary to Act 28/2009 but is harmonized with Presidential Regulation 55/2019 which is a follow-up to the provisions of Article 17 paragraph (1) The Governor's Regulation, as well as through the theory of the welfare state it is understood that the issuance of a statutory regulation must also consider the burden of the government's responsibility in providing for the needs of its people, including by ensuring that people can live in an environment that has good air quality. So in this case, the consistency of the government in harmonizing laws and regulations is needed which is also followed by the participation of local society in supporting government programs to improve the quality of life of the people in their areas.